Improving credit scores for individuals and small businesses: implications for digital bank's credit risk - Yu, Zi Jun (2024)
The rapid growth of digital banking has revolutionized the financial landscape globally, presenting novel opportunities and challenges for individuals and businesses alike. This study investigates the implications of improving credit scores for individuals and small businesses, particularly focusing on the context of digital banks' credit risk in Malaysia. The research methodology employs a descriptive approach, utilizing secondary data sourced primarily from Indian digital banking platforms, considering their emerging relevance to the Malaysian market.